NEGOTIATING THE MANAGEMENT OF MICRO AND SMALL FAMILY BUSINESSES AND THE CARE ECONOMY IN THE POST-SOCIALIST NEOLIBERAL TRANSFORMATION OF SERBIA - Đurić Kuzmanović, Tatjana; Fischer, Jelena; Mandić, Sonja (International Journal of Economic Practice and Policy, 2016)
This paper studies, analyzes and explains the gender bias in the management of family businesses and the care economy in the social and economic context of the post-socialist neoliberal transformation of Serbia. The aim is, from a left-wing feminist theoretical perspective, to point to the fundamental limitations of the dominant patriarchal type of negotiating in achieving the objectives of the development of the national economy, of gender equality, and of the neoliberal transformation of post-socialist Serbia. Gender biases were investigated through in-depth interviews with a sample of thirty micro and small family businesses in Vojvodina/Serbia, in relation to the roles that couples/spouses have in these. The roles of women and men analyzed in this paper are primarily related to the family business management process and negotiations about the distribution of their roles in family businesses and households. The first part of the paper explains the processes of globalization, the global crisis and post-socialist neo-liberal transformation of Serbia and their general effects. The second part of the paper explains the key gender bias identified in the management of micro and small family firms and the care economy. The conclusion points to the key issues and challenges stakeholders in micro and small family firms face, and the need for gender sensitive negotiations in the management of family businesses and households.
Keywords: gender bias; patriarchal management; micro and small family business; households; management of family businesses; allocation of resources in the household; care economy; neoliberal transformation; Serbia